Observation and simulation study on the rapid intensification mechanism of Typhoon “Mekkhala” (2006) - Chen, Dehua; Jiang, Yongcheng; Huang, Xin; Xun, Aiping; Dai, Huaning; Zhang, Hanyun (Frontiers in Earth Science, 2023)
Based on Doppler Weather radar observations and numerical simulations applying the Weather Research and Forecasting (WRF) system, this study focused on the rapid intensification (RI) of Typhoon "Mekkhala" (2006) in the inshore area in 2020. The simulated track of the typhoon relatively matched with the observation, with a slight eastward bias compared to the observed track. During the phase of RI, there was a slight weakening of vertical wind shear between 200-500 hPa. The temporary decrease in vertical wind shear became a favorable factor for the intensification of the typhoon. In general, vertical wind shear of the lower atmosphere is the key to supporting the RI of Typhoon Mekkhala. In the middle troposphere, the southward component of the vertical wind shear suddenly increases, indicates that the inflow of southern wind to the core of the typhoon had strengthened. Thus, the strengthening of the moisture transport by enhanced southern wind, contributed to the intensification of the typhoon. During the intensification of the typhoon, the low-level vorticity was significantly enhanced, and the high vorticity values expanded from the lower to higher troposphere. The vertical distribution of vorticity transformed from symmetry to asymmetry. The development of secondary circulation on both sides of the typhoon is a dynamic factor for intensification.